2022
DOI: 10.1155/2022/4087406
|View full text |Cite|
|
Sign up to set email alerts
|

The Application Value of Three-Dimensional Power Doppler Ultrasound in Fetal Growth Restriction

Abstract: In this study, the application value of three-dimensional power Doppler ultrasound (3D-PDU) in fetal growth restriction (FGR) is explored. The retrospective cohort study enrolled pregnant women (with a gestational week of 11–13 + 6 weeks) who received routine health care in the obstetrics and gynecology clinic of our hospital from January 2020 to January 2021. The placentae were scanned using 3D-PDU, and the subjects were followed up until delivery. The fetuses were divided into the control group (n = 322) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…A restrição do crescimento fetal (RCF), também conhecida como restrição do crescimento intrauterino (RCIU) refere-se à incapacidade do feto de atingir seu potencial de crescimento adequado no útero devido a várias razões adversas. É responsável por cerca de 30% das mortes perinatais e 50% dos lactentes perinatais com hipóxia intrauterina durante o parto, que é a segunda principal causa de mortes perinatais (WANG Y, 2022).…”
Section: Introductionunclassified
“…A restrição do crescimento fetal (RCF), também conhecida como restrição do crescimento intrauterino (RCIU) refere-se à incapacidade do feto de atingir seu potencial de crescimento adequado no útero devido a várias razões adversas. É responsável por cerca de 30% das mortes perinatais e 50% dos lactentes perinatais com hipóxia intrauterina durante o parto, que é a segunda principal causa de mortes perinatais (WANG Y, 2022).…”
Section: Introductionunclassified
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%